The Effect of Local Wisdom-Based Reading Materials on Students’ Motivation in Learning English and Speaking Skills at SMP Kartini 1 Batam - Irwan Herika; Audi Yundayani; Hanna Sundari (EduInovasi: Journal of Basic Educational Studies, 2024)
The issue in this research is framed by students' low motivation to learn English and slow progress in speaking the language. This study aims to determine if using local wisdom-based reading materials affects students' motivation to learn English and their speaking ability because changes are needed to improve their ability. Data collection tools use questionnaires and tests. Data analysis uses SPSS 24 statistics. This type of research is Quasi Experimental with a Nonequivalent Control Group Design. There are two classes for the sample, namely: experimental class and control class. Analysis tests carried out; descriptive test, paired T test. The respondents were 8th graders of SMP Kartini 1 Batam in academic year 2023/2024, totaling 40 students as the population and sample. The research results show that: (1) The results of descriptive tests in the experimental class show that reading material based on local wisdom can motivate students' English learning. The results of the paired T-test show that there is a significant difference on students’ learning motivation in the experimental class compared to the control class. (2) The results of descriptive tests in the experimental class show that reading material based on local wisdom can improve students' speaking skills. The results of the paired T-test showed a significant difference between the speaking skills of students in the experimental class and in the control class. The results show, there is a positive and significant influence of using Local Wisdom-Based Reading Materials to students' motivation in learning English and students' speaking skills.